Smith’s Glasgow lectures: a foundation or an obstacle for the wealth of nations? - Raul Cristóvão dos Santos (Universidade de São Paulo, 1998)
This article argues that the economic argument of Smith’s Glasgow Lectures is embebed with an specific concept of the social organization of production based on the actions of independent producers. This conception gives a theoretical content to the ideas of natural prices, wages, profits and stocks very different from the one found in the Wealth of Nations. As a result, this conception becomes an obstacle for the development of Smith’s economic argument towards his famous work.